(untitled) (Proceedings of the Global Public Health Conference, 2022)
The COVID-19 vaccination is carried out to reduce the morbidity and mortality due to COVID-19, reduce the transmission of COVID-19, and achieve herd immunity. The objective of this study was to determine the relationship between socio-demographic factors and information exposure with the acceptance of COVID-19 vaccine in the community in West Sumatra Province in 2021. This study uses cross-sectional study design. An online questionnaire was distributed to obtain participants ≥18 years old in West Sumatra Province who had never received the COVID-19 vaccine. A total of 266 participants completed the questionnaire form. The acceptance of COVID-19 vaccine was moderate (56,4%). The results showed that there was significant relationship between age (p-value = 0.049) and marital status (p-value = 0.025) with COVID-19 vaccine acceptance. Unmarried people were more likely to accept the COVID-19 vaccine than people who were married / widowed. There was no significant relationship between sex, education, occupation, chronic disease, COVID-19 pasted disease and exposure to information with COVID-19 vaccine acceptance. It is necessary to provide valid and reliable information regarding the COVID-19 vaccine and campaigns that COVID-19 vaccine is needed for all ages.